Restorative Justice in Settling Criminal Case: A Normative-Empirical Study of the Law - Efa Rodiah Nur; Hasan, Zainudin; Dahri, Harapandi (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
Restorative justice offers an alternative framework for addressing the needs of both victims and offenders in Indonesia. While it presents a more hopeful solution compared to traditional punitive measures, concerns about fairness remain. Specifically, victims may feel that the response to the offense does not match the seriousness of the crime, leading to a sense of being undercompensated. This article explores how restorative justice is integrated into Indonesia’s criminal justice system through both normative and empirical legal research. Bandar Lampung serves as the primary focus of this study due to its establishment of a Restorative Justice House and its reputation as a leading practitioners of restorative justice in the country. The research involved observing practices at the District Prosecutor’s Office in Bandar Lampung, allowing for an empirical understanding of how legal regulations are enacted in practice. Additionally, the study reviews the normative aspects of the law related to restorative justice, particularly focusing on the Attorney General’s Regulation No. 15 of 2020 and its Circular No. 1 of 2021 concerning the termination of prosecution based on restorative justice. The findings indicate that restorative justice is primarily applied to lesser criminal cases that fit specific criteria. These cases often involve first-time offenders, crimes that carry potential sentences of at most five years, and financial damages up to Rp 2,500,000. Of the 13 cases examined, 10 were effectively resolved using restorative justice methods. This highlights the potential of restorative justice on repairing harm, addressing victims’ needs, ensuring that offenders take responsibility, and fostering social cohesion. What sets this study apart is its combination of doctrinal legal analysis and fieldwork, enabling a comprehensive evaluation of how restorative justice norms are operationalized within prosecutorial practices in Indonesia.